Recruitment of Rod Photoreceptors from Short-Wavelength-Sensitive Cones during the Evolution of Nocturnal Vision in Mammals - Kim, Jung-Woong; Yang, Hyun-Jin; Oel, Adam Phillip; Brooks, Matthew John; Jia, Li; Plachetzki, David Charles; Li, Wei; Allison, William Ted; Swaroop, Anand (Developmental cell, 2016)
Vertebrate ancestors had only cone-like photoreceptors. The duplex retina evolved in jawless vertebrates with the advent of highly photosensitive rod-like photoreceptors. Despite cones being the arbiters of high-resolution color vision, rods emerged as the dominant photoreceptor in mammals during a nocturnal phase early in their evolution. We investigated the evolutionary and developmental origins of rods in two divergent vertebrate retinas. In mice, we discovered genetic and epigenetic vestiges of short-wavelength cones in developing rods, and cell-lineage tracing validated the genesis of rods from S cones. Curiously, rods did not derive from S cones in zebrafish. Our study illuminates several questions regarding the evolution of duplex retina and supports the hypothesis that, in mammals, the S-cone lineage was recruited via the Maf-family transcription factor NRL to augment rod photoreceptors. We propose that this developmental mechanism allowed the adaptive exploitation of scotopic niches during the nocturnal bottleneck early in mammalian evolution.